THEORETICAL AND PRACTICAL ASPECTS OF IMPLEMENTING BUSINESS CONTINUITY MANAGEMENT SYSTEM AT ENTERPRISES ENGAGED IN PRODUCTION AND TRADE OF CONSTRUCTION MATERIALS IN CRISIS CONDITIONS - Zapukhliak, Ivanna Bogdanivna; Бойко, Марина; Станецький, Олександр (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2025)
The article discusses the theoretical foundations of business continuity management. It is proved that ensuring the functionality of critical business processes, supporting daily operations during or after a threat is the purpose and advantage of business continuity management, especially in martial law. Business continuity management is considered as a management process within which potential business threats are identified, assessed, a prevention plan is formed, the most critical business processes are identified and measures are taken to ensure their rapid recovery, which will ensure the sustainability of the company’s operation and increase its value for stakeholders. The advantages of a business continuity management system are outlined. The components of business continuity management are considered: strategies and policies, business impact analysis, risk assessment, testing and validation, incident identification, disaster recovery. The main factors influencing the construction materials market in Ukraine after the large-scale invasion and future trends are identified. In particular, the main trends include the dominance of domestically produced products, with an insignificant share of imports; a drop in exports; manufacturers’ focus on the domestic market; an increase in public procurement; a change in the leaders of the construction materials market in Ukraine due to the shutdown of production facilities of large companies; and expectations of explosive growth of the construction materials market in Ukraine after the end of the war. Using the principle of building an Ishikawa diagram, the article presents the main business processes of a building materials company and identifies all the risks that arise at each stage. the most critical for the continuous business of building products companies are the lack of qualified personnel and power outages. Power outages cause disruptions in the technological process, and products may be of poor quality. Production downtime also occurs, causing cost overruns in input materials and damage to machinery and equipment. The lack of fuel leads to the curtailment of services such as shipping and unloading and delivery of products. Another problem is the shortage of qualified personnel and their high turnover The study used statistical methods; graphical and tabular techniques to determine the interrelationships of indicators, illustrate them and present the results of the study, and the Ishikawa diagram method.